Optimalisasi Koordinasi Shipper dan Third-Party Logistics (3PL) pada Ekspor Manufaktur Batam - Tasya Cecilia Tasya; Immanuel Zai (Jurnal Abdimas Multidisiplin, 2025)
Purpose: This study aims to optimize coordination between the shipper and third-party logistics (3PL) providers to improve the effectiveness and accuracy of export processes at PT Venturindo Jaya Batam. Export delays and unstructured coordination create inefficiencies, highlighting research gap workflow optimization. Research Methodology: The study was conducted at PT Venturindo Jaya Batam using a qualitative approach. Data were collected through direct observation, interviews with operational and logistics staff, and analysis of non-sensitive operational documents. Data were collected from 6 operational staff and 3 logistics personnel during September–December 2025. The methods applied include process mapping, workflow analysis, and evaluation of coordination practices. Supporting tools such as flowcharts, standard operating procedures (SOP), and checklist templates were designed to support the implementation process. Results: The results indicate that the implementation of a structured export workflow, coordination SOP, and inspection checklist improved clarity in task responsibilities, reduced data inconsistencies, and minimized communication errors between the shipper and 3PL. The export preparation and handover processes became more systematic and controlled. Conclusions: Optimizing coordination through standardized procedures and documentation enhances export efficiency and reduces operational risks. Limitations: This study is limited to one company and uses qualitative data without quantitative performance measurement. Contribution: This study contributes practical insights for manufacturing firms, logistics management practices, and supply chain coordination improvement.